Multilayer-growth of TiAlN/WS self-lubricating composite coatings with high adhesion and their cutting performance on titanium alloy. (15th April 2021) - Li, Guojian; Lü, Wenzhang; Liu, Shiying; Li, Chao; Zhou, Yaoyao; Wang, Qiang
Abstract: Tool coatings with a high coefficient of friction (COF) form a built-up edge between the tool and the piece of work when cutting titanium alloy, creating a high cutting temperature, decreased tool life, and lowing the cutting quality. TiAlN/WS self-lubricating composite coatings with high adhesion were prepared via the multilayer growth of WS with low COF and TiAlN with high wear resistance. The TiAlN/WS coating had high adhesion (135.4 N), low COF (0.261), and unchanged hardness (14 GPa). The low COF and high wear resistance originated from the self-lubricating wear-resistance debris at the micron scale with TiAlN coated with amorphous WS. The coating reduced the adhesive wear. By comparing the machining results of the TiAlN/WS coating with those of the TiAlN coating, the flank wear was 45.9% lower for the same cutting length, the machining speed increased from 41 m/min to 100 m/min, the cutting length was over 200% higher at the same flank wear of 0.3, and the self-lubricating composite coating showed good results under dry cutting conditions. Therefore, this coating provides a method for use in high-speed and environmentally-friendly machines for difficult-to-cut materials.